Primitivism, science, and the Irish revival - Garrigan Mattar, Sinead (Oxford English monographs., 2004)
Covering the works of W.B. Yeats, J.M. Synge and Lady Gregory this text explores the primitivism of the Irish Revival in relation to comparative science.